The Effects of Microwave-Assisted Pretreatment and Cofermentation on Bioethanol Production from Elephant Grass - Sefrinus Maria Dolfi Kolo; Deana Wahyuningrum; Rukman Hertadi (International Journal of Microbiology)
The process of acid hydrolysis using conventional methods at high concentrations results in products having lower yields, and it needs a longer time of process; therefore, it becomes less effective. In this study, we analyzed the effects of microwave-assisted pretreatment and cofermentation on bioethanol production from elephant grass (Pennisetum purpureum). We used a combination of delignification techniques and acid hydrolysis by employing a microwave-assisted pretreatment method on elephant grass (Pennisetum purpureum) as a lignocellulosic material. This was followed by cofermentation with Saccharomyces cerevisiae ITB-R89 and Pichia stipitis ITB-R58 to produce bioethanol. The optimal sugar mixtures (fructose and xylose) of the hydrolysis product were subsequently converted into bioethanol by cofermentation with S. cerevisiae ITB-R89 and P. stipitis ITB-R58, carried out with varying concentrations of inoculum for 5 days (48 h) at 30°C and pH 4.5. The high-power liquid chromatographic analysis revealed that the optimal inoculum concentration capable of converting 76.15% of the sugar mixture substrate (glucose and xylose) to 10.79 g/L (34.74% yield) of bioethanol was 10% (v/v). The optimal rate of ethanol production was 0.45 g/L/d, corresponding to a fermentation efficiency of 69.48%.